GERAKAN FAJAR NUSANTARA (GAFATAR): Krisis Ideologi & Ancaman Kebangsaan - Wildan, Muhammad (TEMALI : Jurnal Pembangunan Sosial, 2019)
The Fajar Nusantara Movement (Gafatar) is an interesting phenomenon in the contemporary era of Indonesia. In the midst of growing rationality and the growth of the world’s mainstream religions, Gafatar was born as a new ’religion’. This article discusses Gafatar as a new form of ideology that was born as a result of the ideological crisis experienced by post-Reformation Indonesians. This paper seeks to trace the history of development and the Gafatar teachings used by this organization to recruit new members. Historically, this research was carried out by reviewing existing books and articles and supported by news in the mass media with the perspective of the messianic movement. This article sees that Gafatar is a reincarnation of the Al-Qiyadah Al-Islamiyah and Komar movements in which Ahmad Musaddeq is the central figure. The main factor in the spread of the Gafatar ideology was people’s disappointment with Indonesia’s economic and political conditions. This is also supported by the ideological crisis factors experienced by some Indonesian people and the weak religious understanding and thirst for spirituality among the middle class. Finally, this article also sees that it is possible to emerge similar movements, so that humanist conflict resolution is needed in order to deal with Gafatar and the schools with certain ideologies that are different from the ideology of the state in the future.